Anti‐Oligomannose Antibodies as Potential Serum Biomarkers of Aggressive Prostate Cancer. Issue 2 (11th February 2013) - Wang, Denong; Dafik, Laila; Nolley, Rosalie; Huang, Wei; Wolfinger, Russell D.; Wang, Lai‐Xi; Peehl, Donna M.
Abstract <table-wrap position="anchor" orientation="portrait"> <x xml:space="preserve">Table </x> Preclinical Research </table-wrap> This study bridges a carbohydrate microarray discovery and a large‐scale serological validation of anti‐oligomannose antibodies as novel serum biomarkers of aggressive prostate cancer (PCa). Experimentally, a Man9‐cluster‐specific enzyme‐linked immunosorbent assay was established to enable sensitive detection of anti‐Man9 antibodies in human sera. A large‐cohort of men with PCa or benign prostatic hyperplasia (BPH) whose sera were banked at Stanford University was characterized using this assay. Subjects included patients with 100% Gleason grade 3 cancer (n = 84), with Gleason grades 4 and/or 5 cancer (n = 204), and BPH controls (n = 135). Radical prostatectomy Gleason grades and biochemical (PSA) recurrence served as key parameters for serum biomarker evaluation. It was found that IgGMan9 and IgMMan9 were widely present in the sera of men with BPH, as well as those with cancer. However, these antibody reactivities were significantly increased in the subjects with the largest volumes of high grade cancer. Detection of serum IgGMan9 and IgMMan9 significantly predicted the clinical outcome of PCa post‐radical prostatectomy. Given these results, we suggest that IgGMan9 and IgMMan9 are novel serum biomarkers for monitoring aggressive progression of PCa. The potential of oligomannosyl antigens as targets for PCa subtyping and targeted immunotherapy is yet to be explored.